SEROPREVALENCIA DE LEPTOSPIROSIS EN ALPACAS DE QUIMSACHATA, PUNO - Santos S., Yván (2009)
The objective of this study was to estimate the prevalence of leptospirosis in alpacas reared in the locality of Quimsachata, Puno during the rainy season (January-March). Serum samples (n=344) of alpacas from the experimental station of the Instituto Nacional de Investigación y Extensión Agraria (INIA) were analyzed using the microaglutination test. The association of age and sex with test results was also evaluated. The overall seroprevalence was 44.8 ± 5.3%. The detected serovars were pomona (43.6%), icterohaemorrhagiae (9.9%), canicola (1.5%), and none for hardjo. Positive samples in young animals («tuis») were nil, whereas in adult animals no statistical differences was found due to sex. The high antibody titres in pomona and icterohaemorrhagiae suggested an active infection during the rainy period.